Prevalence of medical adhesive-related skin injury at peripherally inserted central catheter insertion site in oncology patients. Issue 1 (January 2018) - Zhao, Huihan; He, Yu; Huang, Huiqiao; Ling, Ying; Zhou, Xuemei; Wei, Qin; Lei, Yonghong; Ying, Yanping
Introduction: The aim of our study was to identify the prevalence and risk factors of medical adhesive-related skin injuries (MARSI) at peripherally inserted central catheters (PICC) insertion site in oncology patients. Methods: A cross-sectional observational study lasting two weeks was carried out in four inpatient departments. Skin assessment data and photographs of skin were collected during PICC maintenance. Other related information came from medical records. The skin injuries were classified by dermatologists and PICC specialized nurses. MARSI prevalence was calculated and the associated factors were analyzed statistically. Results: All 419 patients were included. The prevalence of total MARSI at PICC insertion site was 125, (29.83%), including mechanical skin injury (73, 17.42%), contact dermatitis (CD) (39, 9.31%), moisture-associated skin damage (11, 2.63%), folliculitis (2, 0.48%). Multivariate analysis identified two independent risk factors for MARSI including age ≥50 y (p = 0.031, odds ratio [OR] = 4.521, 95% confidence interval [CI] [1.389, 20.620]) and hematologic malignancies (p = 0.000, OR = 2.514, 95% CI [1.590, 3.97]. Oxaliplatin and arsenic trioxide infusion through PICC, history of skin allergies was associated with CD, with p = 0.020, OR = 3.492, 95% CI (1.220, 9.990); p = 0.003, OR = 4.565, 95% CI (1.661, 12.547); p = 0.000, OR = 12.333, 95% CI (3.669, 41.454), respectively. Conclusions: MARSI at PICC insertion site is a frequent event among oncology patients. Epidemiological data and independent risk factors are presented in our study, which provide a basis for future study in this area.